The Domain of Language - Michael Fortescue (Museum Tusculanum Press, 2004)
This book is intended as counter-evidence to the perception that Linguistics is a domain of dusty schoolroom grammar. It follows that linguistics can be characterised differently than as proponents of theoretical orientations who spend their brief breaks from their bone-dry work bashing each other over the head with their various favourite abstractions. The discipline may appear to outsiders as fragmented and - worse still - lacking in relevance to the real world outside its gates. This book demonstrates that Linguistics, in all its varied branches, can be entertaining as well as thought-provoking, and that its domain is indeed a coherent one despite all the internecine squabbling. In an unconventional way, Michael Fortescue introduces his subject as a kind of fable with a historical moral that professional linguists, as well as students, should enjoy as a useful commentary on the state of the discipline today. is a professor of Linguistics at the University of Copenhagen. He is the author of (London, 1998), and (Amsterdam/Philadelphia, 2001).